Analysis of Mathematical Critical Thinking Ability Reviewed from Student Personality - Nisaa, Rhahiliyah Hafza; Septian, Ari; Monariska, Erma (PRISMA, 2024)
This study aims to describe students' mathematical critical thinking skills based on personality types, namely Extrovert and Introvert and to identify personality types that have the highest mathematical critical thinking skills in mathematics learning. This study uses a qualitative descriptive method. The population of the study was grade VIII students of Mts Negeri 6 Cikalongkulon. The subjects of the study consisted of 21 students who filled out a personality questionnaire to determine extrovert and introvert personality types. Data were collected through personality questionnaires, mathematical critical thinking tests in the form of essays, and interviews. Data analysis was carried out using descriptive techniques to classify and explore the level of students' mathematical critical thinking skills. The results showed that students with extrovert personality types had mathematical critical thinking skills in the high category, while students with introvert personality types tended to be in the low category. This study reveals that personality types affect students' mathematical critical thinking skills.